Oncofetal Epigenetic Bivalency in Breast Cancer Cells: H3K4 and H3K27 Tri‐Methylation as a Biomarker for Phenotypic Plasticity. Issue 11 (10th March 2016) - Messier, Terri L.; Boyd, Joseph R.; Gordon, Jonathan A. R.; Stein, Janet L.; Lian, Jane B.; Stein, Gary S.
Abstract : Alterations in the epigenetic landscape are fundamental drivers of aberrant gene expression that contribute to cancer progression and pathology. Understanding specific modes of epigenetic regulation can be used to identify novel biomarkers or targets for therapeutic intervention to clinically treat solid tumors and leukemias. The bivalent marking of gene promoters by H3K4me3 and H3K27me3 is a primary mechanism to poise genes for expression in pluripotent embryonic stem cells (ESC). In this study we interrogated three well‐established mammary cell lines to model epigenetic programming observed among breast cancer subtypes. Evidence is provided for a distinct bivalent signature, activating and repressive histone marks co‐residing at the same gene promoter, in the MCF7 (ESR/PGR+) luminal breast cancer cell line. We identified a subset of genes, enriched for developmental pathways that regulate cellular phenotype and signaling, and partially recapitulate the bivalent character observed in ESC. We validated the biological relevance of this "oncofetal epigenetic" signature using data from ESR/PGR+ tumor samples from breast cancer patients. This signature of oncofetal epigenetic control is an informative biomarker and may provide novel therapeutic targets, selective for both recurring and treatment‐resistant cancers. J. Cell. Physiol. 231: 2474–2481, 2016. © 2016 Wiley Periodicals, Inc.